Is this a cry for help? - Austin, Emily (Emily R.) (Atria Books, 2026)
"Darcy's life turned out better than she could have ever imagined. She is a librarian at the local branch, while her wife Joy runs a book binding service. Between the two of them, there is no more room on their shelves with their ample book collections, various knickknacks and bobbles, and dried bouquets. Rounding out their ideal life is two cats and a sun-soaked house by the lake. But when Darcy receives the news that her ex-boyfriend, Ben, has passed away, she spirals into a pit of guilt and regret, resulting in a mental breakdown and medical leave from the library. When she returns to work, she is met by unrest in her community and protests surrounding intellectual freedom, resulting in a call for book bans and a second look at the branch's upcoming DEI programs. Through the support of her community, colleagues, and the personal growth that results from examining her previous relationships, Darcy comes into her own agency and the truest version of herself."--Provided by publisher.